Mesenchymal stem cells modulate release of matrix proteins from tendon surfaces in vitro: a potential beneficial therapeutic effect - Garvican, Elaine R.; Dudhia, Jayesh; Alves, Ana-Liz [UNESP]; Clements, Lucy E.; Du Plessis, Francois; Smith, Roger K. W. (Future Medicine Ltd, 2014)
Aim: Injury of tendons contained within a synovial environment, such as joint, bursa or tendon sheath, frequently fails to heal and releases matrix proteins into the synovial fluid, driving inflammation. This study investigated the effectiveness of cells to seal tendon surfaces and provoke matrix synthesis as a possible effective injectable therapy. Materials & methods: Equine flexor tendon explants were cultured overnight in suspensions of bone marrow and synovium-derived mesenchymal stems cells and, as controls, two sources of fibroblasts, derived from tendon and skin, which adhered to the explants. Release of the most abundant tendon extracellular matrix proteins into the media was assayed, along with specific matrix proteins synthesis by real-time PCR. Results: Release of extracellular matrix proteins was influenced by the coating cell type. Fibroblasts from skin and tendon appeared less capable of preventing the release of matrix proteins than mesenchymal stems cells. Conclusion: The source of cell is an important consideration for cell therapy.
Keywords: equine; mesenchymal stem cell; synovial fluid; tendon